Case reportPathergy phenomenon in a patient with pyoderma gangrenosum – case report - Wojas-Pelc, Anna; Sułowicz, Joanna; Solecki, Rafał; Nowak, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Pyoderma gangrenosum (PG) is a rare, chronic and relapsing skin disease. In 50-70% of cases it is associated with systemic diseases, most commonly ulcerative colitis or Crohn’s disease. Although lesions are usually limited to the skin, systemic involvement has rarely been reported. Because of the non-specific histological findings, the diagnosis of PG is mainly based on clinical presentation. In 20-30% of patients the emergence of new lesions can be induced by small injuries. In treatment of small lesions local steroids and tacrolimus are used. In patients with a severe disease course systemic treatment is required. Corticosteroids are widely used as initial therapy. In case of lack of response, ciclosporin is recommended. The use of azathioprine, mycophenolate mofetil and biological treatment has also been reported. We present a case of a 48-year-old man with an ulcerative lesion on the left shank. The skin lesion was accompanied by abdominal pain, fever and shivers. According to the CT scan the diagnosis of retroperitoneal abscess was made and a surgical procedure was performed. At the site of the surgical incision, a non-healing skin ulcer appeared. Despite intensive treatment the patient\'s condition worsened, leading to multiorgan insufficiency and death.